2019
DOI: 10.1634/theoncologist.2019-0523
|View full text |Cite
|
Sign up to set email alerts
|

Access to Novel Drugs for Non-Small Cell Lung Cancer in Central and Southeastern Europe: A Central European Cooperative Oncology Group Analysis

Abstract: Background Treatment of non‐small cell lung cancer (NSCLC) improved substantially in the last decades. Novel targeted and immune‐oncologic drugs were introduced into routine treatment. Despite accelerated development and subsequent drug registrations by the European Medicinal Agency (EMA), novel drugs for NSCLC are poorly accessible in Central and Eastern European (CEE) countries. Material and Methods The Central European Cooperative Oncology Group conducted a survey among experts from 10 CEE countries to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…However, access to targeted therapies for NSCLC followed a slower pace, similarly to other Central and Eastern European (CEE) countries. 7,8 This is supported by recently published data reporting a lag time of 14 months between approval of new anti-cancer drugs by European Medicines Agency and a positive national reimbursement decision in Slovenia. 9 Despite significant improvements, the benefits of targeted therapies are still restricted to a small proportion of advanced NSCLC patients who harbour targetable driver mutations.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, access to targeted therapies for NSCLC followed a slower pace, similarly to other Central and Eastern European (CEE) countries. 7,8 This is supported by recently published data reporting a lag time of 14 months between approval of new anti-cancer drugs by European Medicines Agency and a positive national reimbursement decision in Slovenia. 9 Despite significant improvements, the benefits of targeted therapies are still restricted to a small proportion of advanced NSCLC patients who harbour targetable driver mutations.…”
Section: Introductionmentioning
confidence: 73%
“…In our country, reflex testing for particular predictive biomarkers has been adopted in accordance with European guidelines as soon as they were published. However, access to targeted therapies for NSCLC followed a slower pace, similarly to other Central and Eastern European (CEE) countries [7,8]. This is supported by recently published data reporting a lag time of 14 months between approval of new anticancer drugs by the European Medicines Agency and a positive national reimbursement decision in Slovenia [9].…”
Section: Introductionmentioning
confidence: 93%
“…Alectinib, for instance, was first approved in September 2018; however, only in January 2020 was it approved for coverage under the health insurance reimbursement system in China. Moreover, a recent survey showed that alectinib is still not available in majority of countries in central Europe (15). Therefore, patients with ALK-fusion NSCLC will inevitably face the situation that initial treatment resistance of crizotinib and simultaneously had the availability of more potent secondgeneration ALK-TKI as sequential therapy.…”
Section: Crz Baselinementioning
confidence: 99%
“…However, access to these novel drugs is still largely limited mainly because it depends on approval and reimbursement decisions. For instance, a recent survey showed that crizotinib still being the main treatment as alectinib is still not available in the majority of central European countries because of a long lag interval between EMA or national MA and national reimbursement decisions (15). Therefore, we will inevitably encounter the situation that next-generation ALK-TKIs such as alectinib are available for these patients who did still not progress from the initial treatment of crizotinib after alectinib was approval.…”
Section: Introductionmentioning
confidence: 99%
“…An study on access to novel drugs for NSCLC carried out in Central and Southeastern Europe (CEE) concluded that the access to novel drugs was suboptimal in CEE countries and that availability of drugs was not in accordance with their value scores, like the ESMO Magnitude of Clinical Benefit Scale [ 8 ].…”
Section: Introductionmentioning
confidence: 99%